Biosynthesis of Silver Nanoparticles Using Commiphora mukul Extract: Evaluation of Anti-Arthritic Activity in Adjuvant-Induced Arthritis Rat Model - Anupama Singh; Sateesha Shivally Boregowda; Afrasim Moin; Amr Selim Abu Lila; Mohammed F. Aldawsari; El-Sayed Khafagy; Hadil Faris Alotaibi; Rajamma Abburu Jayaramu (Pharmaceutics, 2022)
Rheumatoid arthritis (RA) is a major global public health challenge, and novel therapies are required to combat it. Silver nanoparticles (AgNPs) have been employed as delivery vehicles of anti-inflammatory drugs for RA therapy, and it has been recently realized that AgNPs have anti-inflammatory action on their own. However, their conventional synthesis processes might result in cytotoxicity and environmental hazards. Instead, the use of natural products as a reducing and stabilizing agent in the biosynthesis of silver nanoparticles has arisen as an option to decrease the cytotoxic and environmental concerns associated with chemical synthesis of AgNPs. In this study, we challenged the efficacy of Commiphora mukul (guggul) aqueous extract as a reducing and/or capping agent for the biosynthesis of AgNPs. Guggul-mediated biosynthesized silver nanoparticles (G-AgNPs) were characterized via UV-vis spectroscopy, dynamic light scattering, and scanning electron microscopy. In addition, their anti-arthritic potential was evaluated in an adjuvant-induced arthritis (AIA) model. The fabricated NPs showed an absorption peak at 412 nm, corresponding to the typical surface plasmon resonance band of AgNPs. The synthesized G-AgNPs were nearly spherical, with a particle size of 337.6 ± 12.1 nm and a negative surface charge (−18.9 ± 1.8 mV). In AIA rat model, synthesized G-AgNPs exerted a potent anti-inflammatory action, as manifested by a remarkable reduction in paw volume (>40%) along with elicitation of a minimal arthritic score, compared to control rats. In addition, when compared to arthritic rats, treatment with G-AgNPs efficiently restored the activity of antioxidant enzyme, superoxide dismutase, and catalase, indicating the efficiency of synthesized G-AgNPs in alleviating the oxidative stress associated with RA. Finally, histological examination revealed comparatively lower inflammatory cells infiltration in ankle joint tissue upon treatment with G-AgNPs. Collectively, biosynthesized G-AgNPs might represent a plausible therapeutic option for the management of RA.